The Architecture of Sun Wukong's Image: From Literary Origins to Cultural Representation and Player Identification in the Context of Global Video Games (Architecture Image Studies, 2025)
This study analyzes the transmedia adaptation of the Chinese cultural icon, Sun Wukong (The Monkey King), in global video games, assessing the design methodologies and player reception that enable his evolution from a philosophical literary figure to an interactive digital character. The study employs a sequential explanatory mixed-methods approach, incorporating a systematic content analysis of three major game adaptations with a cross-cultural player survey (N=450). The findings indicate that aesthetic homogenization and the gamification of mythology are two methods for attaining effective global integration. In these instances, the character's functional role and aesthetic attractiveness take precedence over the narrative's fidelity. A semiotic study confirmed the prevalence of cultural stereotyping (e.g., the "Kung-Fu Master" archetype) to enable immediate cross-cultural recognition. Empirical research demonstrates that player identification, regardless of cultural background, is primarily shaped by the character's in-game functional/mechanical role, hence validating the effectiveness of the mechanic-as-myth design approach. The research incorporates these results into a prescriptive model that includes the 80/20 Rule of Fidelity and the "Heroic Primacy" Filter, offering a strategic framework for harmonizing cultural authenticity with commercial viability in the adaptation of non-Western mythological figures into interactive global media.